Some ecologic data on the gastropod rapana thomasiaha crosse along the romanian Black Sea shore - Gomoiu, Marian Traian (Cercetări Marine - Recherches Marines, 2026)
The present paper reports the results of the observations made directly by diving and in aquariums, as well as the biometrical measurements of 390 Rapana thomasiana specimens, collected on the beaches of Mamaia and Agigea. The data found, as compared to those in the literature, show that the predator gastropod Rapana is now gradually invading the Romanian shore, representing a danger for bivalves, especially for rocky mussels.